2017
DOI: 10.1093/abbs/gmx052
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a-5p acts as a negative regulator of TGF-β signaling in skeletal muscle after acute contusion

Abstract: Growing evidence suggests the importance of microRNAs (miRNAs) in stress signaling pathways. Transforming growth factor-β (TGF-β) is a potent cytokine that promotes the development of skeletal muscle fibrosis after acute contusion. However, how miRNAs are involved in TGF-β signaling and confer the robustness of TGF-β-induced fibrotic response remains to be fully elucidated. Here, we demonstrated that miR-146a-5p (miR-146) levels were reduced in a fibrotic mouse model after acute muscle contusion. It was also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 35 publications
1
51
0
1
Order By: Relevance
“…The authors suggested that miR-146a may be a therapeutic option for end-stage renal disease. Sun et al 34 have recently reported that miR-146a acts as a negative regulator of TGF-β signalling in skeletal muscle after acute contusion. In the present study, we confirmed that Smad4 and TRAF6 might also be target genes of miR-146a in orbital fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that miR-146a may be a therapeutic option for end-stage renal disease. Sun et al 34 have recently reported that miR-146a acts as a negative regulator of TGF-β signalling in skeletal muscle after acute contusion. In the present study, we confirmed that Smad4 and TRAF6 might also be target genes of miR-146a in orbital fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was reversely transcribed by using a PrimeScript RT reagent kit (Takara, Dalian, China). For small RNAs, stem loop RT‐qPCR (TaqMan; Thermo Scientific, Wilmington, North Carolina) was used to detect difference in the levels of miRs as previously described . Each sample was run in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Regeneration and fibrosis are the two major challenges for injured skeletal muscle repair. For that reason, studies on post‐injury skeletal muscle repair mostly focused on promoting regeneration and inhibiting fibrosis . In particular, the transforming growth factor‐β (TGF‐β) was extensively studied for its promoting function on muscle fibrosis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, miR-10b-5p was regulated at high levels in atrophying muscles ( Figure 4C). The differentially expressed miRNAs also included the miR-29b-3p, miR-146a-5p, miR-146b-5p, and miR-181c-3p, which have been previously studied in a skeletal muscle context [24,34,35].…”
Section: Mirnas Associated With Muscle Wasting In Cancer Cachexiamentioning
confidence: 99%